The Implementation of Kitab Kuning Learning in Indonesian Islamic Boarding Schools: A Comparison between the Traditional Sorogan Method and Digital-Based Innovations - Ichsan, Rozaq Shohibul; Khoiroh, Hani’atul; Makinuddin, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The study of yellow books is a treasure trove of classical Islamic knowledge and has served as the hallmark and primary identity of Islamic boarding schools education in Indonesia for centuries. Amidst the rapid development of technology and the emergence of a